The Impact of Continuous Professional Teacher Development on Teacher Engagement Levels in Private Family Schools in South Africa - Masha, Anthony Kambi; Agyeman, Nana Yaw Brenya (Studies in Learning and Teaching, 2025)
This was a case study that used a quantitative research approach to gauge educators’ perspectives on how management engages them in continuing professional teachers’ development (CPTD) in private family business schools (PFBSS). The study is set against the background that educators need to be engaged in their jobs for students to excel. However, literature suggests that engagement levels of educators are low in South Africa. A notable reason amongst them is the lack of CPTD. This ensures that schools provide education as a core building block in making South Africa a successful country. Without good schools that prepare young people for the world of work, the problems South Africa faces will remain intractable. Poor results impact the non-actualisation of the Millennium Development Goals, Sustainable Development Goals, National Development Plan, and the African Union’s Agenda 2063. This study examines the link between school-level support and engagement. This is an area that has received little attention in South Africa. The study utilised a non-experimental research design and a positivist paradigm to collect data through structured questionnaires and test the hypothesis using inferential statistics and non-parametric analysis techniques. The study revealed that CPTD predicts engagement levels of educators in PFBSS. The study recommended that educators should be exposed to CPTD sessions often to capacitate them. The study concluded that management in PFBSS should not ignore the human resources development aspect of CPTD.